An unusual finding after adrenal surgery: a case series of adrenal schwannomas - Kostek, Mehmet; Unlu, Mehmet Taner; Caliskan, Ozan; Aygun, Nurcihan; Iscan, Yalin; Dural, Ahmet Cem; Sormaz, Ismail Cem; Tunca, Fatih; Giles Senyurek, Yasemin; Uludag, Mehmet (Frontiers in Surgery, 2023)
Adrenal schwannomas are rare benign tumors with no specific imaging and laboratory findings to diagnose preoperatively. Due to the limited number of cases in the literature, clinical, imaging, and pathological findings are presented in this study. Case 1 is a 61-year-old woman patient who has a 31-mm mass in the right adrenal gland. This mass was nonfunctional; in imaging studies, this mass had a cystic necrotic component, and high 18-fluorodeoxyglucose (FDG) uptake was seen. There was no metaiodobenzylguanidine (MIBG) uptake. Laparoscopic transabdominal right adrenalectomy was performed, and the pathology result was consistent with adrenal schwannomas. Case 2 is a 63-year-old man patient who presented with a 38-mm mass in the left adrenal gland. This mass was nonfunctional and similar to that in Case 1; this mass had a cystic component. Laparoscopic transabdominal left adrenalectomy was performed. The diagnosis of adrenal schwannoma with degeneration was revealed. Case 3 was a 72-year-old woman patient admitted to the hospital for a 125-mm left adrenal mass. Similar to Case 1, this mass also had a cystic necrotic component in imaging studies. High FDG uptake was seen, and the patient underwent conventional adrenalectomy due to the suspicion of malignancy. After pathological evaluation, a diagnosis of adrenal schwannoma was made. A main diagnostic challenge in adrenal schwannomas is the preoperative diagnosis. These masses have no pathognomonic finding or specific hormonal function. Imaging findings of these masses may increase the suspicion of malignancy, which may affect decisions for surgery and the surgical technique.